2017
DOI: 10.7717/peerj.3070
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of least squares regression and geographically weighted regression modeling of West Nile virus risk based on environmental parameters

Abstract: BackgroundThe primary aim of the study reported here was to determine the effectiveness of utilizing local spatial variations in environmental data to uncover the statistical relationships between West Nile Virus (WNV) risk and environmental factors. Because least squares regression methods do not account for spatial autocorrelation and non-stationarity of the type of spatial data analyzed for studies that explore the relationship between WNV and environmental determinants, we hypothesized that a geographicall… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 58 publications
0
25
0
Order By: Relevance
“…WNV was first detected in California in 2003 ( Reisen et al, 2004 ), and then received national attention for the high rates of the disease during the following two years ( Jean et al, 2007 ). Results of WNV vector-borne environmental modeling in California ( Kala et al, 2017 ) let to this study of combining socio-economic data with the results of the environmental model using multivariate geovisualization. This study utilized coarse-scale data (county level) of reported cases of WNV human incidence along with infected dead bird counts as the basis for estimating WNV risk.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…WNV was first detected in California in 2003 ( Reisen et al, 2004 ), and then received national attention for the high rates of the disease during the following two years ( Jean et al, 2007 ). Results of WNV vector-borne environmental modeling in California ( Kala et al, 2017 ) let to this study of combining socio-economic data with the results of the environmental model using multivariate geovisualization. This study utilized coarse-scale data (county level) of reported cases of WNV human incidence along with infected dead bird counts as the basis for estimating WNV risk.…”
Section: Methodsmentioning
confidence: 99%
“…The dataset contained seven variables for each census tract. A single environmental variable (referred to in this study as “mosquito risk”) that represented the results of our earlier GWR model ( Kala et al, 2017 ) was derived from analysis of environmental eight parameters (stream density, surface temperature, surface slope, cultivated land, developed land, road density, vegetation type, evapotranspiration rate). Mosquito risk was found to be statistically significantly related to annual WNV-infected dead birds sentinel data, averaged for the 2004–2010 ( Kala et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, local variations would be ignored in this way and may conclude unreliable results. Therefore, the role of approaches such as GWR becomes highlighted, which capability has been confirmed in comparison to various methods [40,41]. Moreover, it is the first study on leptospirosis performed in Gilan province that uses GIS approaches, and especially GWR.…”
Section: Introductionmentioning
confidence: 94%